IDENTIFIKASI DAN ANALISIS MANAJEMEN RISIKO PADA PROYEK PEMBANGUNAN INFRASTRUKTUR BANGUNAN GEDUNG BERTINGKAT - Nurlela, Nurlela; Suprapto, Heri (Jurnal Ilmiah Desain & Konstruksi, 2014)
The successful implementation of a project undertaken by the construction company associated with the extent to which the project objectives (on time, quality and cost) can be met. By doing risk management is expected to target the right project cost, timely, and appropriate quality in the construction of the building infrastructure can be realized. The purpose of this study was the identification of the causative agent of risk and risk of the Infrastructure Development Project Storey Building and propose an agent handling the most influential risk using the House of Risk (HOR). There are 18 events and the risk of 12 agents / causes of the identified risks. From the calculation, the most influential risk agents are resource procurement process is stopped and has not been rescheduled. Mitigation actions that are at the top of the risk response is the manufacture of a realistic schedule and create a system of monitoring and sanctions. Keywords: Risk management, Project Objectives, deviation costs, House Of Risk (HOR)